Стабилизация за конечное время в задачах со свободной границей для нелинейных уравнений в средах с фрактальной геометрией - Березовский, А.А.; Митропольский, Ю.А.; Шхануков-Лафишев, М.Х. (Український математичний журнал, 2005)
Методом апріорних оцінок встановлено диференціальні нерівності для енергетичних норм в Wˡ₂,ᵣ розв'язків задач із вільними межами в середовищі з фрактальною геометрією для одновимірного еволюційного рівняння і на їх основі отримано оцінки для часу стабілізації T. By using the method of a priori estimates, we establish differential inequalities for energetic norms in Wˡ₂,ᵣ of solutions of problems with a free bound in media with the fractal geometry for one-dimensional evolutionary equation. On the basis of these inequalities, we obtain estimates for the stabilization time T.